2015
DOI: 10.1137/130936889
|View full text |Cite
|
Sign up to set email alerts
|

Random Access to Grammar-Compressed Strings and Trees

Abstract: Abstract. Grammar based compression, where one replaces a long string by a small context-free grammar that generates the string, is a simple and powerful paradigm that captures (sometimes with slight reduction in efficiency) many of the popular compression schemes, including the Lempel-Ziv family, Run-Length Encoding, Byte-Pair Encoding, Sequitur, and Re-Pair. In this paper, we present a novel grammar representation that allows efficient random access to any character or substring without decompressing the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 60 publications
3
118
1
Order By: Relevance
“…We extend some of the results from [8] on querying SLP-compressed balanced parenthesis representations to our context. Specifically, we show that after a linear time preprocessing we can navigate (i.e., move to the parent node and the k th child), compute lowest common ancestors and subtree sizes in time O(log N ), where N is the size of the tree represented by the SLP (Theorem 10).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…We extend some of the results from [8] on querying SLP-compressed balanced parenthesis representations to our context. Specifically, we show that after a linear time preprocessing we can navigate (i.e., move to the parent node and the k th child), compute lowest common ancestors and subtree sizes in time O(log N ), where N is the size of the tree represented by the SLP (Theorem 10).…”
Section: Introductionmentioning
confidence: 91%
“…In [8] it is shown that for a given SLP A of size n that produces the balanced parenthesis representation of an unranked tree t of size N , one can produce in time O(n) a data structure of size O(n) that supports navigation as well as other important tree queries (e.g. lowest common ancestors queries) in time O(log N ).…”
Section: Efficient Tree Operationsmentioning
confidence: 99%
See 3 more Smart Citations